2013
DOI: 10.1007/s10071-013-0682-3
|View full text |Cite
|
Sign up to set email alerts
|

Lemurs and macaques show similar numerical sensitivity

Abstract: We investigated the precision of the approximate number system (ANS) in three lemur species (Lemur catta, Eulemur mongoz, and Eulemur macaco flavifrons), one Old World monkey species (Macaca mulatta) and humans (Homo sapiens). In Experiment 1, four individuals of each nonhuman primate species were trained to select the numerically larger of two visual arrays on a touchscreen. We estimated numerical acuity by modeling Weber fractions (w) and found quantitatively equivalent performance among all four nonhuman pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 85 publications
0
11
0
1
Order By: Relevance
“…All four subjects had participated in several previous experiments, but only two of these involved numerical judgments. In one study, Monkeys B and Y were presented with two stimulus arrays at the left and right of the screen, and were rewarded for touching the array with a greater number of dots (Jones et al, in press). In another unpublished study, Monkey B was presented with two stimulus arrays at the left and right or top and bottom of the screen, and was rewarded for making an eye movement toward the array with a greater number of dots.…”
Section: Discussionmentioning
confidence: 99%
“…All four subjects had participated in several previous experiments, but only two of these involved numerical judgments. In one study, Monkeys B and Y were presented with two stimulus arrays at the left and right of the screen, and were rewarded for touching the array with a greater number of dots (Jones et al, in press). In another unpublished study, Monkey B was presented with two stimulus arrays at the left and right or top and bottom of the screen, and was rewarded for making an eye movement toward the array with a greater number of dots.…”
Section: Discussionmentioning
confidence: 99%
“…In a fitness trait, heritability has been constrained by evolutionary processes (see Merila & Sheldon (1999) for a review of empirical findings relative to fitness and heritability). Further evidence of conservation across species was noted by Jones et al (2014) which found similar levels of ANS acuity between species of lemurs and Old World monkeys. However, while Jones and colleagues (2014) found that mean ANS performance was similar across species, there was also notable individual differences within each species.…”
Section: Introductionmentioning
confidence: 86%
“…Further evidence of conservation across species was noted by Jones et al (2014) which found similar levels of ANS acuity between species of lemurs and Old World monkeys. However, while Jones and colleagues (2014) found that mean ANS performance was similar across species, there was also notable individual differences within each species. Tosto et al (2014) reconciled the contention that ANS is a fitness trait (with low or non-significant heritability shaped by evolution) with the considerable variation within the population by proposing that unique environmental influences drive individual differences.…”
Section: Introductionmentioning
confidence: 86%
“…As in other primates, ring-tailed and mongoose lemurs' ability to discriminate between quantities depends on the ratio between choices being at least 1: 3 or larger to successfully select the larger quantity in a spontaneous food choice task ( table 1 ) [Jones and Brannon, 2012]. In addition, the precision of their approximate number system is comparable to that of rhesus monkeys (Macaca mulatta) [Jones et al, 2014].…”
Section: Introductionmentioning
confidence: 74%